Availability Assessment of Internet of Medical Things Architecture using Private Cloud - Valentim, Thiago; Callou, Gustavo; Vinicius, Alison; França, Cleunio; Tavares, Eduardo (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2023: Anais do L Seminário Integrado de Software e HardwareDO - 10.5753/semish.2023.229386, 2023)
Investments in smart health applications are expected to rise to US$ 960 billion by 2030, and Internet of Things (IoT) have a prominent role in implementing such applications. For instance, hospitals have adopted IoT to collect and transmit patient data to health professionals, as critical patients must be monitored uninterruptedly. Therefore, health systems commonly require high availability, but availability assessment of health systems’ architecture is not a common approach. This paper presents a modeling approach based on generalized stochastic Petri nets (GSPN) to evaluate the availability of Internet of Medical Things (IoMT) architecture based on a private cloud. A case study is adopted to demonstrate the feasibility of the proposed approach.